FOLKLORE IN THE AGE OF ARTIFICIAL INTELLIGENCE: A COMPARATIVE STUDY OF HUMAN AND MACHINE INTERPRETATIONS - Soraya, Andi Inayah; Arafah, Burhanuddin; Ramadhani, Rezky; Abbas, Herawaty (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study aims to compare human and artificial intelligence (AI) responses to Indonesian and English folklore. The Indonesian folklore is represented by Bawang Merah and Bawang Putih as well as Timun Mas, while the English folklore is represented by Cinderella and Jack and the Beanstalk. Employing a descriptive qualitative approach, this research examines reader responses through intellectual, emotional, and cultural dimensions. The study applies the synchronic reception theory, which involves analyzing responses from contemporary human readers in comparison with those generated by AI. The findings reveal a convergence in intellectual responses, where both human readers and AI predominantly exhibit positive interpretations of the four stories. In contrast, emotional responses demonstrate significant variation. Readers show diverse reactions, unlike the more uniform responses generated by AI. These differences are shaped by familiarity with the narratives, as well as cultural, moral, religious, and individual values while AI maintained a consistently positive tone emphasizing narrative coherence without cultural bias. These findings contribute valuable insights to the fields of literary reception studies, cross-entity interpretation, and the implications of technology-assisted literary engagement.